The Impact of Mutation L138F/L210F on the Orai Channel: A Molecular Dynamics Simulation Study - Zhang, Xiaoqian; Yu, Hua; Liu, Xiangdong; Song, Chen (Frontiers in Molecular Biosciences, 2021)
The calcium release-activated calcium (CRAC) channel, composed of the Orai channel and the STIM protein, plays a crucial role in maintaining the Ca2+ concentration in cells. Previous studies showed that the L138F mutation in the human Orai1 creates a constitutively open channel independent of STIM, causing severe myopathy, but how the L138F mutation activates Orai1 is still unclear. Here, based on the crystal structure of Drosophila melanogaster Orai (dOrai), molecular dynamics simulations for the wild-type (WT) and the L210F (corresponding to L138F in the human Orai1) mutant were conducted to investigate their structural and dynamical properties. The results showed that the L210F dOrai mutant tends to have a more hydrated hydrophobic region (V174 to F171), as well as more dilated basic region (K163 to R155) and selectivity filter (E178). Sodium ions were located deeper in the mutant than in the WT. Further analysis revealed two local but essential conformational changes that may be the key to the activation. A rotation of F210, a previously unobserved feature, was found to result in the opening of the K163 gate through hydrophobic interactions. At the same time, a counter-clockwise rotation of F171 occurred more frequently in the mutant, resulting in a wider hydrophobic gate with more hydration. Ultimately, the opening of the two gates may facilitate the opening of the Orai channel independent of STIM.